Legal Responsibilities Of Property Properties And Business Without Local Government License (Surabaya State Court Decision Study Number: 268 /PDT.G/2021/PN.SBY) - Gultom, Aris Sardister (UNIVERSITAS PAKUAN, 2019)
The need for a house (place to live) is a basic human need guaranteed by the constitution of the Republic of Indonesia . This study aims to find out and analyze the legal responsibilities of seminar organizers and speakers followed by paid property business training if the property business seminar and training violates legal provisions. This research uses the type of normative legal research method because the research taken is a juridical analysis related to decisions in a decision, so it can be considered suitable when examined using literature studies and also using decision studies. The actions taken by Cipto Junaidi together with PT Cipta Permata Tiara by holding property business seminars and training have been identified as illegal acts . So as a result of these actions the organizers are required to provide legal accountability because they have caused harm to other people, namely the participants who attended the seminars and training held .